Maintaining Political Rights Equality - Adoniati Meyria Widaningtyas; Windu Darojat (Journal of Contemporary Sociological Issues, 2023)
Most of the blind in Indonesia live in vulnerable, underdeveloped and poor conditions due to restrictions, barriers, difficulties, and reduction or elimination of the rights of disabilities. In Indonesia there are 3.5 million blind people. Of the existing number, 80% already have the right to vote in the 2019 elections. However, blind people have not been able to carry out elections in accordance with the principles of LUBER, Honest and Fair. They must get assistance from other parties or people in casting their votes at the TPS. This is prone to fraud, manipulation and leakage of options. RASA MESRA innovation is a ballot template that helps the blind in punching ballots without the need for assistance from other people. RASA MESRA is designed to be easily oriented by blind people. The button provided on RASA MESRA will provide an audio explanation according to the writing on the ballot papers. With the existence of RASA MESRA, people with blind sensory disabilities can be independent in determining their voting rights, reduce fraud and manipulation of votes, and guarantee equal rights of persons with disabilities in accordance with the principles of LUBER, Honest and Fair. RASA MESRA was initiated by PPSDSN Penganthi Temanggung. Keywords: blind people, disability, political rights, innovation, Rasa Mesra